Genetic diagnosis of intellectual disability and its ethical aspect - Kępińska Walczak, Zofia (Warszawskie Studia Pastoralne, 2018)
The article presents a reflection on the genetic diagnosis of intellectual disability. Attention was drawn to the moral aspect of genetic testing and it was emphasized that genetic diagnosis must not become an instrument in the implementation of bio-utilitarianism or the concept of wrongful life, according to which, whether a person can be considered a human being, and thus have the right to life, depends on certain factors, and is not self-evident by the very fact of belonging to the human species.